Primary care visits for asthma monitoring over time and association with acute asthma visits for urban Medicaid-insured children. (November 2014) - Nelson, Kyle A.; Garbutt, Jane M.; Wallendorf, Michael J.; Trinkaus, Kathryn M.; Strunk, Robert C.
Abstract Objectives: To examine the association between numbers of primary care provider (PCP) visits for asthma monitoring (AM) over time and acute asthma visits in the emergency department (ED) and at the PCP for Medicaid-insured children. Methods: We prospectively enrolled 2–10 years old children during ED asthma visits. We audited hospital and PCP records for each subject for three consecutive years. We excluded subjects also receiving care from asthma subspecialists. PCP AM visits were those with documentation that suggested discussion of asthma management but no acute asthma symptoms or findings. PCP "Acute Asthma" visits were those with documentation of acute asthma symptoms or findings, regardless of treatment. ED asthma visits were those with documented asthma treatment. Generalized liner models were used to analyze the association between numbers of AM visits and acute asthma visits to the ED and PCP. Results: One hundred three subjects were analyzed. Over the 3 years, the mean number of AM visits/child was 2.5 ± 2.3 (standard deviation), range 0–10. Only 50% of subjects had at least 1 PCP visit with an asthma controller medication documented. The mean number of ED asthma visits/child was 3.2 ± 2.8; range 1–18. The mean number of PCP Acute Asthma visits/child was 0.7 ± 1.6; range 0–11. Increasing AM visits was associated with more ED visits (estimate 0.088; 95% CI 0.001, 0.174), and more PCP Acute Asthma visits (estimate 0.297; 95% CI 0.166, 0.429). Increasing PCP visits for any diagnosis was not associated with ED visits (estimate 0.021; 95% CI −0.018, 0.06). Conclusions: Asthma monitoring visits and documented controller medication for these urban Medicaid-insured children occurred infrequently over 3 years, and having more asthma monitoring visits was not associated with fewer ED or PCP acute asthma visits.